KEDUDUKAN ASHOBAH DALAM ILMU FAROIDH MENURUT PERSPEKTIF HUKUM ISLAM - Ris Dwi Yuliani; Safira Tsaniyatur Rohaimi; Naila Rizqi Salsabila; Najwa Nur Hanifah; Mohammad Syaifudin (Konsorsium Dosen Institut Agama Islam Al-Yasini Pasuruan, 2025)
This research aims to analyze the position of ashabah in Islamic inheritance law (faraidh), focusing on its legal foundations, classifications, and role in ensuring fairness in the distribution of inheritance. The study employs a library research method by collecting and reviewing relevant literature, including the Qur’an, hadith, classical and contemporary fiqh works, as well as scholarly articles, which are then examined using content and descriptive analysis. The findings show that ashabah refers to heirs whose shares are not fixed in the Qur’an or hadith but who receive the remainder of the estate after the fixed shares of dzawil furudh are distributed. Ashabah is classified into three main types: ashabah binafsih (male heirs by themselves), ashabah bilghair (female heirs who become ashabah due to the presence of male heirs), and ashabah ma‘al-ghair (female heirs who become ashabah together with other female heirs). Their status is highly significant, as they may inherit the entire estate, a part of it, or sometimes nothing, depending on the composition of other heirs. The study concludes that a correct understanding of ashabah is essential to achieving justice in inheritance distribution and preventing disputes, thus reinforcing the proper application of Islamic law.